The Concept of Restitutive Guarantee in Employment Relations: Normative Reconstruction of Training Bonds and Cost Recovery Agreements in Indonesia - Iwan Riswandie; Imam Syafa'i (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Job training has become a strategic investment in contemporary employment relations, yet the absence of clear regulatory frameworks governing training cost reimbursement in Indonesia generates legal uncertainty and normative tensions between employers and employees. Practices such as training bonds and cost recovery agreements often blur the distinction between legitimate investment protection and restrictions on labor mobility. This study aims to develop a normative reconstruction of training cost reimbursement through the concept of restitutive guarantees. This research employs a normative legal approach, combining statutory, conceptual, and limited comparative analyses, complemented by hypothetical normative illustrations as a normative stress test to assess the legitimacy of workers’ financial obligations in structurally asymmetric employment relationships. The findings demonstrate that training cost reimbursement is normatively justifiable only when it is limited to actual, verifiable, proportionate, and unamortized costs, and when it functions as a restitution mechanism rather than a contractual penalty. The proposed concept of restitutive guarantees establishes a coherent legal framework grounded in the principles of proportionality, transparency, and non-coercion. This study contributes to labor law discourse by clarifying the legitimate boundaries of workers’ financial obligations and offering a normative model that reconciles employer investment protection with workers’ freedom of mobility. It also provides a conceptual basis for future labor law policy development in Indonesia within an internationally relevant framework.